English lecturers’ perception in teaching English with public speaking skill - Lestari, Sisilia Endah; Kristiawan, Yohanes Angie (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
An English lecturer is an education professional who serves as a role model for language learners, instilling a sense of proficiency and inspiration within the students. A compelling role model is required to effectively deliver materials with public speaking skills. Therefore, a set of qualifications and expertise that inspire confidence and trust among the students is necessary for the English lecturer. Despite being aware of the essential role of public speaking in language teaching, English teachers may exhibit apathy towards its incorporation into their classroom practices. This study aims to explore the English lecturers’ experience and perception toward teaching English with public speaking skill in university level. This study’s subjects were five English lecturers from Yogyakarta and Bangka Belitung. The English lecturers were asked to state their opinion about their perception of the importance of public speaking to be employed in their teaching process, how it influenced the students’ engagement during the class, and other successful teaching factor to build the students’ interest. This study applied a qualitative descriptive approach by using semi-structured interview with the five English lecturers as an instrument to collect data. The writer analysis results indicated that the English lecturers had positive perceptions towards public speaking skill in teaching English. Meanwhile, several other essential aspects that contribute significantly to a well-rounded language education could be applied such as lecturers’ language proficiency, interpersonal skills, lesson planning and organization. Two previous studies, conducted by Afriani & Silvia (2020) and Supraptiningsih & Ahmad (2020), respectively, diverged from addressing the topic of public speaking skills in their exploration of lecturers' perceptions and professional development. Public speaking abilities were notably absent from their investigations.Main finding of this study is the English lecturers have positive perception and belief that their public speaking skills support their teaching techniques. For further studies, more elaboration of public speaking techniques would enrich the English lecturers’ knowledge in teaching with skills of effective speaking.